2011
DOI: 10.1002/jmri.22474
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric magnetic resonance urography

Abstract: Magnetic resonance urography (MRU) is a powerful clinical tool that fuses anatomic information with functional data in a single test without the use of ionizing radiation. This article provides an overview of the technical aspects, as well as common clinical applications with an emphasis on the evaluation of hydronephrosis. A fluid challenge is an essential part of our MRU protocol and enables the definition of compensated or decompensated kidneys within the spectrum of hydronephrosis. This classification may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 51 publications
(63 reference statements)
0
27
0
2
Order By: Relevance
“…The Patlak-Rutland plot method must take into account the input function estimated from heart and lung ROI measurements at RS (7) and from an ROI in the abdominal aorta at DCE MR urography (22,28). Other functional criteria at DCE MR urography have been published (1,5,11,(14)(15)(16), such as the slope of the uptake curve, the volume of contrast-enhancing renal parenchyma, the transit time between the cortex and the upper ureter and the 2-3-minute ratio of uptake as functional parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Patlak-Rutland plot method must take into account the input function estimated from heart and lung ROI measurements at RS (7) and from an ROI in the abdominal aorta at DCE MR urography (22,28). Other functional criteria at DCE MR urography have been published (1,5,11,(14)(15)(16), such as the slope of the uptake curve, the volume of contrast-enhancing renal parenchyma, the transit time between the cortex and the upper ureter and the 2-3-minute ratio of uptake as functional parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic pulse sequences performed after injection of an intravenous bolus of gadolinium chelates (ie, dynamic contrast material-enhanced [DCE] MR urography) have been used to calculate the percentage of SRF from time-intensity curves. Investigators (1,5,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) have reported significant correlation of DCE MR urographic results with SRF derived from radioscintigraphy in a number of single-center studies. Two methods have been developed to calculate the SRF from the time-intensity curve: (a) the area under the curve (AUC) method (18)(19)(20) and (b) the Patlak-Rutland method, which is currently the reference method used with RS (7).…”
Section: Settings and Participantsmentioning
confidence: 99%
“…The indication for surgery generally depends on imaging criteria, requiring a few months of follow‐up of the patients. Renal function and kidney morphology data are evaluated by renal ultrasound, renal scintigraphy and, more recently, uro‐magnetic resonance imaging (uro‐MRI) . These investigations are non‐invasive, but poorly predict the optimal timing of surgery and renal recovery after surgical repair.…”
Section: Introductionmentioning
confidence: 99%
“…Other protocols currently proposed 15 favour 3D spoiled gradientecho sequences providing higher spatial resolution. However, longer acquisition times of repetitive 3D measurements are more susceptible to breathing artefacts, which are particularly evident in older children.…”
Section: Discussionmentioning
confidence: 99%